2010
DOI: 10.5194/nhess-10-1927-2010
|View full text |Cite
|
Sign up to set email alerts
|

Benefitting from differences in knowledge, practice and belief: Māori oral traditions and natural hazards science

Abstract: Abstract.This paper builds upon earlier work that argued the information and experience contained within the knowledge-practice-belief complex of Mātauranga Māori [Māori knowledge] is a valuable and neglected area of information and understanding about past catastrophic events in Aotearoa/New Zealand (A/NZ). Here we map Māori oral traditions (pūrākau) that relate experience with extreme environmental disturbance (in particular, tsunamis) around the A/NZ coast, compare the findings with geoarchaeological eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…For example, King and Goff (2010) suggest that indigenous knowledge and oral history (in this case, Māori oral history of tsunami) can be used to guide researchers to locations where new geological studies of past events can be carried out to contribute to our understanding of risk. With respect to preparedness, Carter-Pokras et al (2007) undertook a study of the preparedness of Latin-American immigrants in the USA and found that few people had received information about emergency preparedness and most did not have emergency plans.…”
Section: Relevance Of Culture For Drrmentioning
confidence: 98%
“…For example, King and Goff (2010) suggest that indigenous knowledge and oral history (in this case, Māori oral history of tsunami) can be used to guide researchers to locations where new geological studies of past events can be carried out to contribute to our understanding of risk. With respect to preparedness, Carter-Pokras et al (2007) undertook a study of the preparedness of Latin-American immigrants in the USA and found that few people had received information about emergency preparedness and most did not have emergency plans.…”
Section: Relevance Of Culture For Drrmentioning
confidence: 98%
“…Research questions in natural hazard studies have changed dramatically since 1958, notably in the following six ways. Few of these, however, have been pursued by physical geographers (Hewitt being a notable Canadian exception): In what ways do underdevelopment and vulnerability influence natural hazard studies (e.g., Sen ; Hewitt ; Cutter )? In what ways do considerations of risk perception and management transform natural hazard studies (e.g., Whyte and Burton ; Slaymaker )? Can the distinction between “natural” and “man‐made” hazards be sustained (e.g., Burton and Hewitt ; Burton et al ; Smith )? What is the role of technological and political conflict in natural hazard studies (e.g., Glickman et al ; Hewitt ; Dauvergne )? What is the role of differences in knowledge, practice, and beliefs in natural hazard analysis (e.g., King and Goff )? Do natural hazards raise questions of unfair, inequitable impacts on society and involve the redressing of injustices (e.g., Sen )? …”
Section: The “Real World” As Perceived By Physical Geographersmentioning
confidence: 99%
“…It is quite often argued that the information and experience contained within the knowledge-practice-belief complex of communities and individuals is a most valuable, but often neglected area of information and understanding about past catastrophic events (King and Goff, 2010). This apparent mismatch is also made obvious by Shah (2006) as he addresses the importance of and issues related to the so-called Last-Mile.…”
Section: Achievements and Lessons Learnedmentioning
confidence: 99%